SEJARAH JALUR KERETA API DI RIAU PADA TAHUN 1943-1945 - Riyanty, Ade Dewi; ', Prof. Dr. H. Isjoni, M.Si; ', Drs. Kamaruddin,M.Si (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The entry of Netherlands to Indonesia makes changes totransportation in Indonesia. Netherlands planned the development of transportation,especially train. The first railway was built during governor general Mr. L.A.J. BaronSloet van den Beele era. This railway connects Kemijen village and Tanggung village(Semarang, Central Java). West Sumatera was also one of the Netherlands plans todevelop their railway. This plan of making railway would connect the East coast andthe West coast of Sumatra that eventually covers the entire island of Sumatera. The planof making railway was in Sawahlunto and going through Muaro Sijunjung, gold mineLogas, Pekanbaru up to the Strait of Malacca. However, while the position changedfrom the Netherlands to Japan, those plans could not be realized by the Netherlands.Japan at the time was in the World War 2 felt they need to strengthen their defense,especially by building the railways, airfields and other development of their defense toface the second World War. In this case the construction of railways that will bediscussed is in Riau. This study aims to determine (1) What factors are drivingNetherlands made the planned to construct railways in West Sumatra. (2) The processof power shift in Indonesia from the Netherlands to Japan in 1943. (3) The Intention ofJapan to build Railways that was planned by the Netherlands. (4) Japanese atrocitiesduring the construction of Railways in Riau. (5) The fate of the Railway constructionworkers in Riau. This research was conducted by using Historocal Research. Thismethod was systematically arranged every step in the sequential way: Heuristics,Interpretation and historiography. The results of this study indicate that theconstruction of railways in Riau is one of the people's struggle for the sake ofIndonesia's Independence.Keywords: Railway, The construction of railway, Riau